KETIKA MIMBAR KEHILANGAN ARAH: EVALUASI KHOTBAH TANPA PRINSIP HOMILITIKA DAN HERMENEUTIKA - Yoses Yulianus Tetelepta (Berajah Journal, 2026)
The pulpit ministry has an important role in the growth of the faith of the congregation, but in practice there are often deviations due to the neglect of the principles of homiletics and hermeneutics. This research aims to examine the phenomenon of sermons that are not based on the rules of proper biblical interpretation and are not conveyed systematically and theologically. The method used is descriptive qualitative through the study of literature from various sources of practical theology and contemporary homiletics. The results show that many preachers today tend to place more emphasis on subjective experience than on the correct exposition of the Bible text. The effect is a weakening of the authority of God's word in the life of the church. Therefore, it is necessary to restore the function of the pulpit through the application of structured homiletic principles and responsible hermeneutics. This research emphasizes that quality sermons must be biblical, contextual, and applicative, so as to be able to build the spiritual life of the congregation as a whole.